Reframing Special Education: Reclaiming Effective Education - Smith, Robin M. (Disability Studies Quarterly, 2006)
Rice's analysis of New York Times editorials illustrates ways in which disability is constructed to promote public policy that maintains the status quo. I propose that George Lakoff's work can be useful in understanding how power structures operate, specifically in regard to disability issues. Lakoff suggests that language frames the debate differently for those who value a "nurturant parent model" than for those who value a "strict father model" for family and national governance. I conclude by explicating how an application of Lakoff's "language frames" to disability discourse might help progressives identify and recapture the public discourse on education and disability.